The relationship between the use of mobile application and job performances of support staff at Kuching Port Authority, Sarawak/ Syarfieza Sharidan - Sharidan, Syarfieza (2018)
In today’s dynamic business environment, the usefulness of mobile application has increased greatly in recent years which it allows users to perform more tasks in a mobile context. It has huge impact towards employee’s job performance. Poor usefulness of mobile application leads to many disastrous things such as lack of motivation, poor performance and poor communication. This reduces work quality, job satisfaction productivity and inefficiency. The objectives of this study are to investigate the relationship between the perceived usefulness, perceived ease of use and behavioural intention of mobile applications (WhatsApp) and job performance among support staff in Kuching Port Authority. The target population of this research is 150 support staff of Human Resource and Development and Human Resource Management at Kuching Port Authority, Sarawak.